2020
DOI: 10.2174/1570159x18666200122122512
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress and Metal Toxicity in the Progression of Alzheimer’s Disease

Abstract: : Alzheimer’s disease (AD) is one of the life-threatening neurodegenerative disorders in the elderly (>60 years) and incurable across the globe to date. AD is caused by the involvement of various genetic, environmental and lifestyle factors that affect neuronal cells to degenerate over the period of time. The oxidative stress is engaged in the pathogenesis of various disorders and its key role is also linked to the etiology of AD. AD is attributed by neuronal loss, abnormal accumulation of Amyloid-β (Aβ) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 125 publications
0
38
0
Order By: Relevance
“…Chen et al [11] found that the compound AB42chelated metals such as iron and copper and decreased metal-induced Aβ aggregation (Figure 3 and Table 2).…”
Section: Metal Accumulation and Metal Ion Dyshomeostasismentioning
confidence: 97%
See 3 more Smart Citations
“…Chen et al [11] found that the compound AB42chelated metals such as iron and copper and decreased metal-induced Aβ aggregation (Figure 3 and Table 2).…”
Section: Metal Accumulation and Metal Ion Dyshomeostasismentioning
confidence: 97%
“…In vitro In vivo can pass BBB [47] Monogalactose group inhibits Aβpeptide aggregation In vitro possibility to optimize the uptake across the BBB via the glucose transporter mechanism [11] The introduction of flexible moieties at the linker inhibit β-sheet aggregation and fibril formation…”
Section: Ref Modification Of Curcumin Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increase in OS could be generated through the deregulation of metal homeostasis (Sayre et al, 2000 ), and there is evidence that metal-induced OS promotes Aβ deposition and tau pathology in AD (Greenough et al, 2013 ; Birla et al, 2020 ; Wang et al, 2020 ). At least partially, OS in AD has been linked to the impairment of copper homeostasis.…”
Section: Copper As An Os-inducer In Admentioning
confidence: 99%